Analysis of Internal Conflict in the Novel Suraya by Nafi'ah Al Ma'rab - Sindi Lesmana; Roziah Roziah (Universitas Trunodjoyo Madura, 2026)
This study explores the internal conflicts experienced by the central characters in Nafi’ah Al-Ma'rab's novel, Suraya. By positioning the novel as a literary representation of human life and imagination, the research aims to analyze the protagonist's struggle with self-understanding, identity, and interpersonal relationships, specifically focusing on the psychological dynamics of coping with emotional pressure. A qualitative approach with a descriptive-analytic method was employed. The study utilizes literary psychology as the primary lens, specifically applying Albertine Minderop’s theory on emotion classification to categorize and interpret the characters' internal struggles. The analysis reveals that the internal conflicts in Suraya are manifested through five distinct emotional dimensions: (1) profound guilt, (2) self-punishment as a coping mechanism, (3) paralyzing shame, (4) deep-seated sadness, and (5) the complexities of love. These emotions drive the narrative tension and dictate the characters' psychological evolution throughout the story. The study concludes that the internal conflicts in the novel serve as a critical vehicle for understanding human resilience. By mapping these emotional states, the research demonstrates how literary works provide profound insights into the universal human experience of navigating internal turmoil and emotional adversity.